Characterization of signal transmission over integrated satellite and Li-Fi network for high-speed rail environment in tropical region - Maniam, P. M. Kalai Vaanan (2021)
Malaysia High-speed railway (MyHSR) communications will become a key feature supported by intelligent transportation communication systems under the 4th Industrial Revolution for On-The-Move (OTM) internet access. Congestion in the radio spectrum, big data bandwidth networking issues and requirement of smaller antenna sizes simulating greater interest in the underutilized Ka frequency band. However, transmission at these shorter wavelengths is greatly influenced by signal noise resulting in signal attenuation and decreased link availability. The main innovation is to improve the throughput and bandwidth load balancing between Ka-band High Throughput Satellite (HTS) space communication and heterogeneous hybrid Light Fidelity (Li-Fi) in tropic. In line with this, the objective is proposing of an approach of a Ka-band satellite signal attenuation expectation. The strategy also considering disabilities experienced during climate elements for tropical area and high portability situation on the High-Speed Rail (HSR) application. The second part of the thesis compromises network integration, by enhancing the throughput and handover performance on both Satcom and Li-Fi. The process involves designing the indoor hybrid Li-Fi channel model where there is an exploration on the feasibility of utilizing a half breed HTS satellite and Li-Fi network for OTM application. In the third part, this thesis takes advance steps by focusing in achieving better satellite-Li-Fi backhaul network integration for both On-The-Pause and On-The-Move developments. The methods focused on this approach, supported with a novel experimental, Proof of Concept (PoC) and validation of a heterogeneous satellite-Li-Fi network. This is done by managing the bandwidth and throughput capacity under the Deep Packet Inspection (DPI) model. Finally, an analysis led, a reliable channel performance in tropical area for mobility application has been identify with an improvement of 19.52 % in overall receiving Packet Loss Ratio (PLR) including enhancement on the network throughput by 67.24% while carrying out DPI solution during unfavorable climate condition.